Normothermic Machine Perfusion Enhances Intraoperative Hepatocellular Synthetic Capacity: A Propensity Score-matched Analysis. Issue 7 (July 2019) - Ionescu, Mihnea-Ioan; Tillakaratne, Suchintha; Hodson, James; Gunson, Bridget; Nasralla, David; Pinter Carvalheiro da Silva Boteon, Amanda; Sermon, Kate; Mergental, Hynek; Isaac, John R.; Roberts, John K.; Muiesan, Paolo; Friend, Peter; et al.
Abstract : Background: Normothermic machine perfusion (NMP) of liver grafts is increasingly being incorporated in clinical practice. Current evidence has shown NMP plays a role in reconditioning the synthetic and energy capabilities of grafts. Intraoperative coagulation profile is a surrogate of graft quality and preservation status; however, to date this aspect has not been documented. Methods: The liver transplantation recipients who received NMP liver grafts in the QEHB between 2013 and 2016 were compared in terms of intraoperative thromboelastography characteristics (R time, K time, α-angle, maximum amplitude, G value, and LY30) to a propensity score-matched control group, where the grafts were preserved by traditional static cold storage (SCS). Results: After propensity matching, none of the thromboelastography characteristics were found to differ significantly between the 72 pairs of SCS and NMP organs when measured preimplantation. However, postimplantation, NMP organs had significantly shorter K time (median: 2.8 vs 3.6 min, P = 0.010) and R + K time (11.4 vs 13.7 min, P = 0.016), as well as significantly larger α-angle (55.9° vs 44.8°, P = 0.002), maximum amplitude (53.5 vs 49.6 mm, P = 0.044), and G values (5.8 vs 4.9k dynes/cm 2, P = 0.043) than SCS organs. Hyperfibrinolysis after implantation was also mitigated by NMP, with fewer patients requiring aggressive factor correction during surgery (LY30 = 0, NMP vs SCS: 83% vs 60%, P = 0.004). Consequently, NMP organs required significantly fewer platelet units to be transfused during the transplant procedure (median: 0 vs 5, P = 0.001). Conclusions: In this study, we have shown that NMP liver grafts return better coagulation profiles intraoperatively, which could be attributed to the preservation of liver grafts under physiological conditions.